Children's Geographies: Tracing The Evolution and Involution of a Concept. Issue 1 (1st January 2018) - Aitken, Stuart C.
Abstract: This essay traces the evolution of children's geographies as a concept through three phases. First, in the early 1970s as a beginning impression influenced heavily by developmental and environmental psychology. Second, beginning around 1990, children's geographies cohered politically as geographers focused on young people's identity through feminism and Marxism, and global policy initiatives on children's rights. The third phase, covering the last couple of decades, coming from issues of political identity, challenges what we think we know about young people and their geographies, and also advocates a set of loose theories about the ways young people create and re‐create spaces and themselves. Cognate disciplines coming to geography for insights about children and their worlds characterize this current phase. To offset this seeming linear progression the essay also notes an involution of the concept that defies clear categories and sequences, but suggests the fluidity of tensions and accommodations that comprises children's geographies.